Development and Implementation of a Pediatric Palliative Care Program in a Developing Country - Doherty, Megan; Thabet, Chloé (Frontiers in Public Health, 2018)
Palliative care is recognized as an important component of care for children with cancer and other life-limiting conditions. In resource limited settings, palliative care is a key component of care for children with cancer and other life-limiting conditions. Globally, 98% of children who need palliative care live in low- or middle-income countries, where there are very few palliative care services available. There is limited evidence describing the practical considerations for the development and implementation of sustainable and cost-effective palliative care services in developing countries. Objectives: Our aim is to describe the key considerations and initiatives that were successful in planning and implementing a hospital-based pediatric palliative care service specifically designed for a resource-limited setting. Setting: Bangabandu Sheikh Mujib Medical University (BSMMU) is a tertiary referral hospital in Bangladesh. Local palliative care services are very limited and focused on adult patients. In partnership with World Child Cancer, a project establishing a pediatric palliative care service was developed for children with cancer at BSMMU. Results: We describe 4 key elements which were crucial for the success of this program: 1. Raising awareness and sensitizing hospital administrators and clinical staff about pediatric palliative care 2. Providing education and training on pediatric palliative care for clinical staff 3. Forming a pediatric palliative care team 4. Collecting data to characterize the need for pediatric palliative care. Conclusions: This model of a hospital-based pediatric palliative care service can be replicated in other resource-limited settings and can be expanded to include children with other life-limiting conditions. The development of pilot programs can generate interest among local physicians to become trained in pediatric palliative care and can be used to advocate for the palliative care needs of children.